Sustainable supply chains in the agricultural sector: Adding value instead of just exporting raw materials. Corporate due diligence within a coherent, overarching and partnership-based EU strategy - Bettina Rudloff; Christine Wieck (Stiftung Wissenschaft und Politik (SWP), 2020)
The corona pandemic has placed supply chains back on the agenda. The economic repercussions spotlight the complexity of today's global division of labour. Current German and European initiatives are seeking to tighten the responsibility of final business consumers for human rights and sustainability in their supply chains. The objective is to enforce sustainable production in sovereign third countries. In the case of agriculture these explicitly supply chain-based approaches need to be backed up by improvements in the European Union's trade, investment and agricultural policies. Influencing agricultural supply chains in such a way as to overcome their specific sustainability and human rights problems will require all approaches to be combined. Currently, conventional approaches treat supply chains in isolation, and only address imports flowing into the EU. As such, they consider developing countries exclusively in their traditional role as suppliers of raw agricultural commodities and ignore options for increasing local value added and fostering development.
Keywords: 320